Energy Equality in Indonesia Villages: A Discourse Analysis - Manurung, Elvy Maria; Diyanah, Mumsikah Choyri; Permatasari, Paulina; Wardhana, Irwanda Wisnu (International Journal of Energy Economics and Policy, 2022)
This study aims to uncover the program of energy independence in Indonesia villages by the government for several decades. as a development program phenomenon of energy use and the development of its sources in the developing villages in Indonesia. The areas selected for observation are four rural areas outside Java, namely the state of Central Sulawesi, West Kalimantan, Halmahera, and East Nusa Tenggara. Interview results show that not all villagers understand energy term and there are still rural areas that do not have access to energy sources. Using discourse analysis as a qualitative method and Amartya Sen’s theory of development as a freedom, this study shows that energy development still unequal in Indonesia Villages. Development as an extension of human freedom requires a more comprehensive goal. This study recommends that development plans must focus on the main rights of citizens to survive and have reason to live. Villagers have the right to obtain facilities and resources equal to those of urban residents, especially in energy access equity, and to live in prosperity.